Recent Advances in the Cycloaddition Reactions of 2‐Benzylidene‐1‐benzofuran‐3‐ones, and Their Sulfur, Nitrogen and Methylene Analogues - Deng, Qingsong; Meng, Xiangtai (Chemistry, an Asian journal, 2020)
Benzothiophene, benzofuran, indole, and indene derivatives are privileged heterocyclic motifs. These are present in a wide range of bioactive natural products and pharmaceutical drugs and are the subject of materials science research. However, the construction of benzothiophene, benzofuran, indole, and indene frameworks have been long‐standing challenges to organic chemists. In this review, we classify the derivatives of four structures synthesized from 2‐benzylidene‐1‐benzofuran‐3‐one and their analogues in terms of their ring size (from three‐ to ten‐membered) and type (fused or spiro), as well as summarizing the developments of this field. Finally, we discuss the ring opening and 1,4‐addition reactions. 2‐Benzylidene‐1‐benzothiophen‐3‐ones and their analogues are versatile reagents for cycloaddition reactions. Benzothiophene, benzofuran, indole, and indene derivatives are obtained after the cycloaddition. This minireview summarizes the recent advances in this area.